2021
DOI: 10.1016/s2542-5196(21)00151-0
|View full text |Cite
|
Sign up to set email alerts
|

Family policy and food insecurity: an observational analysis in 142 countries

Abstract: Summary Background Levels of child malnutrition and hunger across the world have decreased substantially over the past century, and this has had an important role in reducing mortality and improving health. However, progress has stalled. We examined whether family policies (eg, cash transfers from governments that aim to support households with children) are associated with reduced food insecurity. Methods In this observational analysis, we used a dataset o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…It is noteworthy, however, that the greatest reduction in severe food insecurity was observed among low-income families (Brown & Tarasuk, 2019). This is consistent with findings from a large international comparative study showing that more generous cash transfer programs for families with children have the greatest impact on food insecurity among families at the bottom of the income distribution and reduce the most severe forms of food insecurity (Reeves et al, 2021). Yet our results indicate that food insecurity remains a serious problem for Canadian families.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is noteworthy, however, that the greatest reduction in severe food insecurity was observed among low-income families (Brown & Tarasuk, 2019). This is consistent with findings from a large international comparative study showing that more generous cash transfer programs for families with children have the greatest impact on food insecurity among families at the bottom of the income distribution and reduce the most severe forms of food insecurity (Reeves et al, 2021). Yet our results indicate that food insecurity remains a serious problem for Canadian families.…”
Section: Discussionsupporting
confidence: 90%
“…Household food insecurity, defined as inadequate or insecure access to food due to financial constraints, is a serious public health problem in many high-income countries, including Canada. This problem disproportionately affects families with children (Reeves et al, 2021). Based on the 2018 Canadian Community Health Survey, the most recent nationally representative data available, one in five 12-17 year-olds lived in a household affected by some level of food insecurity, compared to one in ten adults 50-64 years of age and almost one in twenty adults 65 and older (Polsky & Garriguet, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…These social protection measures contribute directly or indirectly to improving the socioeconomic status of families, consequently reducing HFI. Additionally, measures must be implemented that include educating vulnerable groups, such as women and girls, improving access to drinking water, and changing access to maternal and child health care (Durao et al, 2020;Reeves et al, 2021). Brazil's policies for income redistribution and the provision of basic services, including universal access to education, health, water supply, and sanitation services, played a fundamental role in improving child growth indicators from 1996 to 2007, highlighting the need to maintain economic and social policies (Monteiro et al, 2009;Monteiro et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with a study conducted in the city of Salvador, Brazil, that found stronger associations of food insecurity in households living in areas with more disadvantaged conditions, 25 and reports from North America finding similar results. 8 , 26 Households with children have been shown to have a higher prevalence of food insecurity 5 , 27 which might make them more vulnerable to their contextual conditions and calls for attention for a closer assessment of this association.…”
Section: Discussionmentioning
confidence: 99%